Syphilitic aortitis: from the past to the present (view of a dermatovenerologist) - S.V. Zakharov; T.V. Svyatenko; V.K. Zakharov; V.V. Gorbuntsov; L.A. Pohrebniak (Medičnì Perspektivi, 2024)
In order to improve the diagnosis and treatment of syphilitic aortitis, an analysis of known data on the clinical manifestations, course and diagnosis of this pathology was conducted, illustrating our own observations with the subsequent implementation of recommendations in clinical practice. The problem of syphilitic aortitis - the most frequent manifestation of late syphilis - was considered. Current data on clinical manifestations, possibilities and problems of diagnosing this pathology were presented. Modern methods of serological research used in the diagnosis of syphilitic aortitis were analyzed in detail; the course, complications and prognosis of this pathology were separately considered. All these aspects were illustrated by our own observations of clinical cases of syphilitic aortitis, which are of interest due to their rarity in clinical practice and demonstrate the importance of correct diagnosis and appropriate treatment. Serological tests for syphilis, ultrasound examination of the heart, extracardiac vessels and internal organs; X-ray examinations were used when examining patients. It was concluded that lesions of the cardiovascular system are currently among the most common forms of visceral syphilis. Syphilitic aortitis with symptoms of cardiovascular damage, which are caused by aortic valve insufficiency, narrowing of the ascending coronary arteries, aneurysmal dilatation of the ascending part and aortic arch, occurs in the late stages of syphilitic infection. Even in patients with syphilis who have been treated in the past with penicillin drugs, cardiovascular damage may occur, namely aortitis with aortic valve insufficiency. The most informative methods for detecting late cardiovascular damage are: enzyme-linked immunosorbent assay, passive hemagglutination reaction, immunoblotting and computed tomography of the heart and echocardiography. Special attention is paid to the fact that the uniqueness of the above observations lies in the fact that complicated forms of aortitis began to occur more often and also in treated syphilis patients who had previously been treated with water-soluble penicillin. Aortitis also occurs against the background of seroconversion (positivity) of non-treponemal tests, which were previously negative after treatment.